2009
DOI: 10.1192/bjp.bp.107.048686
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent-onset anorexia nervosa: 18-year outcome

Abstract: The 18-year outcome of teenage-onset anorexia nervosa is favourable in respect of mortality and persisting eating disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
229
4
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(258 citation statements)
references
References 27 publications
18
229
4
7
Order By: Relevance
“…Current evidence points to a strong role for three particular deficits, impaired theory of mind (Caglar-Nazali et al, 2014;Davis et al, 2016 ), weak central coherence (Lang et al, 2014), and deficits in executive functions, including problems in set-shifting (Roberts et al, 2007;Tchanturia et al, 2012;Westwood et al, 2016). Social interaction impairments and reciprocal communication deficits, which are key symptoms of ASD, have also been reported in ED patients (Wentz et al, 2009;Zucker et al, 2007). Moreover, a recent review by Huke and colleagues (2013), investigating autistic traits in EDs, found that nearly 23% of individuals with an ED displayed autism spectrum traits.…”
Section: Autistic Traits In Clinical Eating Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence points to a strong role for three particular deficits, impaired theory of mind (Caglar-Nazali et al, 2014;Davis et al, 2016 ), weak central coherence (Lang et al, 2014), and deficits in executive functions, including problems in set-shifting (Roberts et al, 2007;Tchanturia et al, 2012;Westwood et al, 2016). Social interaction impairments and reciprocal communication deficits, which are key symptoms of ASD, have also been reported in ED patients (Wentz et al, 2009;Zucker et al, 2007). Moreover, a recent review by Huke and colleagues (2013), investigating autistic traits in EDs, found that nearly 23% of individuals with an ED displayed autism spectrum traits.…”
Section: Autistic Traits In Clinical Eating Disordersmentioning
confidence: 99%
“…The importance of assessing empathising can be seen in the impaired theory of mind (Caglar-Nazali et al, 2014) and social interaction deficits, which are key symptoms in ED patients (Wentz et al, 2009;Zucker et al, 2007). The studies assessing empathising in EDs have mainly used two distinct measures to assess empathy, the Interpersonal Reactivity Index (Davis, 1983), a multi-dimensional assessment of empathy, and the Empathising Quotient (EQ; [Baron-Cohen and Wheelwright, 2004]), a measure of empathy used to account for the social and communication barriers commonly found in individuals with ASD.…”
Section: Empathisingmentioning
confidence: 99%
“…Bei 70% erfolgte eine Genesung von der Essstörung, 10% litten unter chronifizierter Anorexia nervosa und bei 20% trat im Verlauf eine bulimische oder atypische Essstörung auf. Allerdings scheint die Prognose der kindlichen Anorexia nervosa wiederum schlechter zu sein als bei der adoleszenten Form [62,63].…”
Section: Verlauf Und Prognoseunclassified
“…32 Wentz et al showed that autistic traits in childhood were found to be predictive of a poor global outcome in the eating disorder in adulthood. 33 • 35 • In assessing whether a person has AN, attention should be paid to the overall clinical assessment (repeated over time), including rate of weight loss, growth rates in children, objective physical signs and appropriate laboratory tests.…”
Section: Dsm-5 Diagnostic Criteria -American Psychiatric Association mentioning
confidence: 99%